Consumption of dopamine receptor 1 agonist SKF-38393 reduces constant-light-induced hyperactivity, depression-like, and anxiety-like behaviors in a sex specific manner in C57BL/6J mice - Guindon, Grace E.; Anzalone, Alexis; Burke, Samantha G.; Murphy, Cloey A.; Milano, Maria E.; Price, John C.; Tadros, Stephanie; McFarland, Alexander T.; Contini, Fernanda Medieros; Seggio, Joseph A. (Frontiers in Behavioral Neuroscience, 2025)
Artificial light exposure during nighttime, including constant light (LL), is an increasingly prevalent environmental occurrence linked to impaired mood and cognitive impairments in both humans and animal models. Dopamine and dopamine 1 receptors are well known to modulate circadian rhythms and mood. This study investigated the effects of LL on anxiety-like, depressive-like, and cognitive behaviors in male and female C57BL/6J mice and assessed whether consumption of SKF-38393, a dopamine 1 receptor agonist, can mitigate these negative behavioral outcomes. Mice were exposed to LL or a standard 12:12 light:dark cycle (LD) for 6 weeks, with subgroups receiving either SKF-38393 or water. All mice had their circadian rhythms continuously monitored and were placed within behavioral tests that assayed their anxiety-like, depressive-like, and learning and memory behaviors. Behavioral assays revealed that LL increased hyperactivity and anxiety-like behaviors, which were mitigated by SKF-38393 consumption in both sexes. In addition, male mice exhibited anhedonia under LL, which was alleviated by SKF-38393, whereas female mice were resistant to LL-induced anhedonia. Sex differences emerged in fluid consumption independent of lighting condition, with females consuming more SKF-38393, and in responses to DA on behavior, including novel object recognition and exploration. These results indicate that low dose oral consumption of dopamine 1 receptor agonists can ameliorate some of the negative behavioral effects of LL exposure. This study highlights the complex interplay between chronic light, dopamine, and sex in influencing mood and behavior, suggesting potential modulatory roles for dopamine 1 receptor agonists in regulating behavioral outcomes to circadian disturbances.